Overweight and obesity screening indicator using neck circumference - Harjatmo, Titus Priyo; Dumaria, Corazon Hanna; Nareswara, Anastu Regita (International Journal Of Community Medicine And Public Health, 2023)
Background: Overweight and obesity can be assessed through anthropometric measurements using the body mass index (BMI). Some studies suggest that neck fat is positively correlated with visceral fat, insulin resistance, and metabolic syndrome. Neck circumference has been shown to be closely correlated with BMI and can be used as a practical screening tool for identifying overweight or obese individuals in both men and women. However, the correlation of neck circumference with measurements of body fat percentage in obesity has not been studied. Methods: This study is an analytical study that conducted sensitivity and specificity analyses of neck circumference to describe indicators of overweight and obesity in children. Data collected included neck circumference, weight, height (converted into BMI), and other characteristics of the children. Neck circumference measurements were taken using neck circumference tape. Results: The results showed that the body weight of school-age children had an average of 28.3 kg. Height had an average of 133.2 cm. Neck circumference measurements had an average of 30.3 cm. The correlation analysis using the Pearson product moment test showed a significant value of r=0.483 and p=0.00. Conclusions: There is a significant relationship between neck circumference and BMI. The greater the neck circumference, the greater the BMI, and the area under the curve (AUC) of the ROC curve indicates that neck circumference is a better diagnostic tool for identifying BMI. The results of the ROC curve showed a UAC value of 0.783, indicating that neck circumference can diagnose obesity with an accuracy of 78.3%.